Reaching the Finish Line: Personality and Persistence in Post-secondary Education - Wilson, Claire A.; Dave, Hiten; D’Costa, Malvika; Babcock, Sarah E.; Saklofske, Donald H. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
Few studies have examined the contribution of individual psychological factors to long-term indicators of academic success.This study examines the influence of personality and individual difference factors in relation to retention. In this study, 290 Canadian undergraduate students completed measures of personality, resiliency, perfectionism, and trait Emotional Intelligence in the first semester of their first year, and enrolment status was collected at the end of each academic year for four years. Multinomial logistic regression analysis indicated that only high school grade point average (GPA) and being male predicted a higher likelihood of withdrawing from the program or delaying degree completion, compared to those who completed. The need for future studies with larger samples and consideration of more complex relationships between factors is highlighted.